Genetic differentiation and postglacial migration of the Dactylorhiza majalis ssp traunsteineri/lapponica complex into Fennoscandia - Olofsson, Sofie; Hedrén, Mikael (Plant Systematics and Evolution, 2008)
Eight variable regions (microsatellites, insertion/deletion and duplication regions) from the plastid DNA genome were analyzed for 91 populations belonging to Dactylorhiza majalis ssp. traunsteineri and closely related taxa. A total of 36 composite plastid haplotypes were found. The two dominating haplotypes had a clear geographic distribution suggesting at least two separate immigration routes into Scandinavia after the last glaciation: one southwestern route and one or two southeastern routes. D. majalis ssp. traunsteineri could not be clearly separated from any of the other taxa included in the study except for D. majalis ssp. sphagnicola. The morphologically similar taxa D. majalis ssp. traunsteineri, D. majalis ssp. lapponica and D. majalis ssp. russowii showed no genetic differentiation, and therefore we suggest an amalgamation of the three taxa into one broadly circumscribed subspecies; D. majalis ssp. lapponica. The plastid data also revealed incidents of hybridization and possible introgression between D. majalis ssp. lapponica and other members of the genus, e.g., D. incarnata.